Association of myocardial work indices with controlled arterial hypertension, age, weight and conventional echocardiographic parameters in women. (4th February 2022) - Jasaityte, R; Bajraktarevic, R; Blaschke-Waluga, D; Seeland, U; Regitz-Zagrosek, V; Stangl, K; Knebel, F; Stangl, V; Brand, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Objective: By incorporating myocardial deformation and afterload, novel echocardiographic myocardial work indices appear to be advantageous over the load-dependent left ventricular (LV) strain. As such, these indices might provide a better and load-independent estimation of LV function in patients with chronically increased afterload. To date, however, little is known about the relation of these indices to clinical and conventional echocardiographic parameters. Purpose: Our aim was to evaluate the relationship between myocardial work indices and age, weight, conventional echocardiographic parameters, and the presence of previously defined well-controlled arterial hypertension (AH) in women without cardiovascular diseases. Methods: We retrospectively analyzed echocardiographic data of women, included to the BEFRI (BErlin Female RIsk evaluation) trial. Global Work Index (GWI), Global Constructive Work (GCW), Global Wasted Work (GWW) and Global Work Efficiency (GWE) were calculated using commercially available software based on noninvasive pressure-strain loops. Mulitvariate analysis of covariance was applied to investigate the relation of myocardial work indices with the above mentioned variables. Results: A total of 224 women were included in the final analysis. 155 of them were normotensive and 69 had controlled AH. Women with AH were significantly older (67 ± 12 y. vs. 54 ± 13 y, p < 0.05), had higher blood pressure (136 ± 10/77 ± 6 mmHg vs. 121 ± 7/70 ± 6 mmHg, p < 0.05), higher body mass index (28 ± 5 kg/m² vs. 24 ± 4 kg/m², p < 0.05), thicker LV walls (septum: 12 ± 2 mm vs. 9 ± 1 mm; posterior wall: 11 ± 1 mm vs. 9 ± 1 mm, p < 0.05 for both), higher left atrial volume index (35 ± 8 ml/m² vs. 29 ± 5 ml/m², p < 0.05) and longer IVRT (103 ± 27 ms vs. 85 ± 24 ms, p < 0.05). LV ejection fraction, LV internal dimensions and TAPSE were within a normal range and did not differ between groups. Patients with AH showed lower global longitudinal strain (GLS) (19 ± 3% vs. 20 ± 2%, p < 0.05), higher GWI and GCW (2214 ± 285 mmHg% vs. 2045 ± 244 mmHg%, 2445 ± 316 mmHg% vs. 2256 ± 272 mmHg%; p < 0.05 for both) (Fig. 1), whereas GWW and GWE did not differ significantly (112 ± 59 mmHg% vs 101 ± 51 mmHg% and 95 ± 3% vs. 95 ± 2%). In the multivariate analysis GWI and GCW, but not GWW or GWE, were significantly positively associated with the presence of AH (s. Table). Besides that, GWI and GCW were positively related to LVEF and LVEDD. GWW showed negative relation to LVEF and a positive relation with IVRT. GWE was positively related to LVEF, and negatively to IVRT. None of the indices was significantly related to age. Conclusion: We have defined the relationship of various myocardial work indices with weight, conventional echocardiographic parameters, and the presence of AH. The higher GWI and GCW in patients with AH might suggest higher energetic expenditure of myocardium due to increased afterload. The prognostic impact of these findings remains to be defined.